AUDITUL INOVAȚIONAL LA BIBLIOTECA MUNICIPALĂ „B.P. HASDEU”* - GOLBAN, Facultatea de Jurnalism și Științe ale Comunicării, USM, Elena (BIBLIOPOLIS, 2020)
The idea of innovation audits conducting within a public library that offers public services arised from the fact that in this sector of activity a budget deficit is typically recorded, and innovation audits may suggest some solutions for modernization and more efficient management of resources. Innovation audits’ methodology is developing during last 30-40 years in American and European regions, but for R. Moldova this concept is brand-new. Moreover, taking into account the fact that there is no official body for „innovation audits” which would promote an unique methodology, conducting such type of audits is considered to be an individual task of each organization. This study is an attempt of quantitative and qualitative approach of the innovation phenomenon at the Municipal Library „B.P. Hasdeu” and aims a methodology that would measure the innovation potential and its constituents.